the new science of health and happiness: investigating buddhist engagements with the scientific study of meditation - Wilson, Jeff (Zygon, 2018)
Clinical and neuroscientific studies of Buddhist meditation practices are frequent topics in the news media, and have helped certain practices (such as mindfulness) achieve mainstream cultural status. Buddhists have reacted by using these studies in a number of ways. Some deploy the studies to show the compatibility of science and Buddhism, often using the authority of science to lend credence to Buddhism. Other Buddhists use meditation studies to demonstrate the superiority of Buddhism over science. Within inter-Buddhist debates, meditation studies are used to argue for changes in practice or belief, but also sometimes to reinforce certain traditional practices. Benjamin Zeller's threefold categorization of religious groups' attitudes toward science (guide, replace, absorb) and José Ignacio Cabezón's three ideal types of relationships between Buddhism and science (conflict/ambivalence, compatibility/identity, complementarity) contribute to analysis of Buddhist uses of scientific studies of meditation.